Analysis of community local wisdom based on tourism potential in ambon city and central maluku district, Maluku Province - Muspida, Muspida; Meteko, Stellamaris; Matitaputy, Izaac Tonny (Jurnal Ekonomi, 2024)
This writing aims to look at the perceptions of the community in Maluku, especially in Negeri Latuhalat, Ambon City and Negeri Suli in Central Maluku Regency, specifically identifying the impact of local wisdom of the community and knowing the perception of the community regarding the importance of preserving their country with local wisdom of the community in managing natural resources. has the potential to be developed as a tourist destination. The analytical method is an activity carried out continuously during the research period. Data collection methods include observation, interviews, questionnaires, documentation and FGD. The results obtained are local wisdom related to conservation, mutual cooperation or masohi work, sasi culture and tax payment or ngase in Suli State, Ambon City and Latuhalat State, Central Maluku, all of which are included in the "very good" criteria.